Ethical Reflexivity in Research with (Migrant) Children: Dealing with Power Asymmetries to Build up More Participatory Approaches - Anne Carolina Ramos; Catrin Heite; Andrea Riepl; Luisa Weissberg; Nina Bingham; Yara Küng; Alexandra Roggensinger; Julia Steiner (Societies)
Participatory research with children presents a range of ethical challenges, particularly concerning power dynamics between adults and children in the research process. Factors such as the research setting, parental consent, the role of gatekeepers, interview dynamics, and the methods used can either facilitate or limit children’s participation. For migrant children and their families, specific issues like the language of communication, the materials developed for the study, socio-economic status, and migration-related vulnerabilities, such as sensitive experiences of (forced) migration, are especially important. This paper explores these ethical considerations through the lens of our research in the WoKidS project, which examines the subjective well-being of children (N = 84) aged 8 to 14, both with and without a migration background. The article is grounded in an ethical reflexivity approach, where multiple researchers involved in the study reflect on their experiences and practices while conducting research with (migrant) children.